Parâmetros de qualidade da água e índice trófico em micro bacia de abastecimento hídrico no noroeste do Rio Grande do Sul - Silva, Darlan Weber da (2022)
Characterized as a vital element for life, water plays an important role in maintaining the quality of life of all species, whether human or animal, as well as maintaining life in the environment. It is in this way that the search for potable and quality water becomes so important, since this vital asset is found in only 2.5% of all available water on the planet, where within that, a large part is inaccessible for consumption. At the same time, the demand for water grows considerably each year, and along with that, there is a growing concern with the preservation of water sources such as rivers and streams, as these are the main points of water abstraction, whether for urban or rural populations. When dealing with population growth and advancement over water sources, another situation is presented to us. The loss of water quality due to the advancement of communities, consequently triggers the proliferation of microorganisms and other water pathologies. These sources should be the direct target of monitoring and surveillance actions, culminating in collection and analysis activities and education throughout these areas. In this context, analyzing the local reality of the Municipality of Frederico Westphalen, in Rio Grande do Sul, more specifically of five microbasins, here called Microbasins A,B,C,D and E, all of which contribute to Lajeado do Pardo, the main stream of abstraction of water for the local population, there is the possibility of a more in-depth study about the quality of the water distributed to the population, where the objective is to evaluate the Trophic State index, an important indicator of the enrichment of the concentration of nutrients, mainly of Phosphorus and Nitrogen, which in excess, end up increasing the development and growth of microalgae and, finally, of bacteria that cause environmental degradation and significant loss of quality of the sources. Through the study, there is a greater presence of organisms in areas with a higher percentage of agricultural area with occurrence of rainfall. Evaluation parameters are used to determine the quality of sources, such as evaluation of levels of Nitrite, Nitrate, Ammonia, Phosphorus, Escherichia coli, Coliforms in addition to the Trophic State Index. When determining the Trophic State Index, it is verified that the presence of nutrients does not show interference of use as a function of water quality. Precipitation, on the other hand, can cause an increase in NO2-, and NH3 levels within the watersheds. There is still the presence of Escherichia coli and Coliforms within the evaluated watersheds, however all in a non-high degree. In some watersheds where there is an altered level of contamination, there is a large presence of polluting agents, as is the case of swine and poultry activities. These are responsible for a high production of organic waste, which is easily transported by rains into water courses, consequently causing their contamination along the basin. With this protection measures and regular assessment of the quality levels of water sources becomes important, aiming at water quality for future generations.